Persepsi Orangtua tentang Penggunaan Smartphone untuk Anak Usia Dini - Khan, Rosa Imani; Dwiyanti, Linda (Universitas Nusantara PGRI Kediri, 2022)
This study aims to examine the description of parents' perceptions of smartphone use for early childhood. Based on survey results, in this era of digitalization, the use of smartphones by early childhood cannot be denied. The use of smartphones for early childhood besides having a positive impact will also have a negative impact. Perception as well as the role of parents is the main factor that can determine the extent to which the positive and negative impacts are exposed to the child. This research is a survey research that aims to provide an explanation (explanatory research) with 50 parents/guardians of kindergarten students as respondents. The data collection tool used was a parental perception questionnaire about smartphone use for early childhood, consisting of 20 items, with a reliability coefficient of 0.801. Data analysis to be used is descriptive statistical techniques. The data from this study explain that in general the parents who are the subjects of this study know and understand the functions and benefits of smartphones and their positive and negative impacts on children. Parents do not like it if their children play smartphones too often because it has a negative impact on aspects of children's development. Although they don't always accompany their children when using smartphones, parents make efforts to minimize these negative impacts, including not relying on smartphones to accompany their children, applying certain rules when children use smartphones, guiding children to take advantage of the positive side of smartphones, limiting applications. smartphones used by children and teach children how to use smartphones properly and correctly.